2002
DOI: 10.1007/s00213-001-0979-9
|View full text |Cite
|
Sign up to set email alerts
|

Infralimbic kappa opioid and muscarinic M1 receptor interactions in the concurrent modulation of anxiety and memory

Abstract: (1) The effects of IL infusions of norBNI or pirenzepine (10 nmol/0.5 microl) alone on anxiety-like behaviour and aversive learning and memory in the elevated plus-maze replicated previously reported data. (2) Mixed M1/kappa receptor inhibition in the IL cortex exerted counteractive effects on anxiety-like behaviour and aversive learning in the elevated plus maze. (3) Mixed M1/kappa receptor inhibition appeared to exert additive disruptive effects on alternation performance and aspects of attention related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 64 publications
1
66
2
Order By: Relevance
“…It is conceivable that the deficits in novel object recognition may be attributable to endogenous opioid-mediated deficits in attention. Reports have shown that administration of exogenous KOR agonists suppress attention in a model of fear conditioning (Iordanova et al, 2006) and increase omissions and correct response latencies in a fivechoice serial reaction time task (Paine et al, 2007), although KOR antagonist (nor-BNI) administration was also shown to disrupt aspects of attention related to working memory in mice (Wall and Messier, 2002). The novel object recognition test may be configured differently to examine attention (Silvers et al, 2007), but the present study did not examine this effect.…”
Section: Discussioncontrasting
confidence: 55%
“…It is conceivable that the deficits in novel object recognition may be attributable to endogenous opioid-mediated deficits in attention. Reports have shown that administration of exogenous KOR agonists suppress attention in a model of fear conditioning (Iordanova et al, 2006) and increase omissions and correct response latencies in a fivechoice serial reaction time task (Paine et al, 2007), although KOR antagonist (nor-BNI) administration was also shown to disrupt aspects of attention related to working memory in mice (Wall and Messier, 2002). The novel object recognition test may be configured differently to examine attention (Silvers et al, 2007), but the present study did not examine this effect.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition, antalarmin treatment normalized stress-increased same arm return ratio (treatment: F 1, 24 ¼ 8.757, p ¼ 0.007; interaction: F 1, 24 ¼ 4.663, p ¼ 0.041; Figure 5b), which reflects certain aspects of attention (Wall and Messier, 2002;Wietrzych et al, 2005). In each sample phase of the temporal order memory test, all groups of mice explored the two copies of an identical object similarly (Supplementary Figure S7d).…”
Section: Blockade Of Crf 1 Prevents Early-life Stress-induced Cognitimentioning
confidence: 88%
“…The total distance traveled, number of arm entries, spontaneous alternation ratio (Wang et al, 2013), and same arm return ratio (Wall and Messier, 2002;Wietrzych et al, 2005) were measured.…”
Section: Behavioral Testingmentioning
confidence: 99%
“…However, performance of all mutant mice remained above the chance level, which for Y-maze performance, is calculated at 22.2%. Furthermore, the error analysis showed that reduced performance in the Y-maze correlated for doubleand RXR␥ single-mutants with a higher number of alternate arm returns and not with the same arm returns, thus being a further indication of reduced attention/working memory in these mutant animals (Holcomb et al 1999;Wall and Messier 2002). Thus, the reduction of spontaneous alternation indicates that in agreement with results from DNMTP test, an inactivation of RXR␥ alone or in parallel with RAR␤ leads to reduction, but not complete absence of spatial working memory.…”
Section: Discussionmentioning
confidence: 99%
“…For efficient alternation, mice need to use working memory, and thus, they should maintain an ongoing record of most recently visited arms, and continuously update such a record. A mouse with an impaired working memory cannot remember which arm it has just visited, and thus shows decreased spontaneous alternation (Holcomb et al 1999;Wall and Messier 2002).…”
Section: Y-maze Spontaneous Alternationmentioning
confidence: 99%